Spontaneous regression of tumour and the role of microbial infection--possibilities for cancer treatment - Kucerova, Petra; Cervinkova, Monika (Anti-cancer drugs, 2016)
This review deals with the role of microorganisms in spontaneous regression of a tumour. Spontaneous cancer regression is a phenomenon that has been described for many centuries. One of the most well known methods of inducing spontaneous regression of cancer is the application of Coley's toxin (heat-killed Streptococcus pyogenes and Serratia marcescens), which has been used for the successful treatment of sarcomas, carcinomas, lymphomas, myelomas and melanomas. In clinical practice, the use of Bacillus Calmette-Guérin vaccine for the treatment of superficial urinary bladder cancer is the most common instance of the application of microorganisms for the treatment of cancer. This review provides further information on other tested bacteria--Clostridium spp., Bifidobacterium spp., Lactobacillus spp. and Salmonella spp.--in this field of study. Among new age methods, bactofection, alternative gene therapy, combination bacteriolytic therapy and bacteria-directed enzyme prodrug therapy are some of the potential cancer treatment modalities that use microorganisms. We have also provided information about the interconnection among microorganisms, immune system response, and the possible mechanisms involved in the spontaneous regression of tumours.
Keywords: fyziologie bakterií; kombinovaná terapie; dějiny 19. století; Humans; History, 19th Century; Genetic Therapy; lidé; History, 17th Century; dějiny starověku; Clostridium; genetická terapie; spontánní regrese nádoru; History, 18th Century; Bacterial Toxins; History, Ancient; Neoplasms; Lactobacillus; dějiny 18. století; nádory; BCG Vaccine; Neoplasm Regression, Spontaneous; bakteriální toxiny; BCG vakcína; Bifidobacterium; dějiny 17. století; Bacterial Physiological Phenomena; Combined Modality Therapy; Salmonella